2017
DOI: 10.1128/mcb.00206-17
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Small Critical Regions of Swi1 Conferring Prion Formation, Maintenance, and Transmission

Abstract: contains several prion elements, which are epigenetically transmitted as self-perpetuating protein conformations. One such prion is [ ], whose protein determinant is Swi1, a subunit of the SWI/SNF chromatin-remodeling complex. We previously reported that [ ] formation results in a partial loss-of-function phenotype of poor growth in nonglucose medium and abolishment of multicellular features. We also showed that the first 38 amino acids of Swi1 propagated []. We show here that a region as small as the first 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The identification of [SWI + ] and Swi1 as its prion determinant in yeast was the first identification of a global transcriptional regulator being able to form a prion (Du et al 2008). A small, asparagine-rich extreme amino-terminal region has been described as the major determinant of [SWI + ], and the ability of this region to propagate and maintain [SWI + ] is notable (Crow, Du and Li 2011;Valtierra, Du and Li 2017). [SWI + ] has also displayed important and varied interplay with other yeast prions including [PSI + ] and [RNQ + ]-developing the knowledge regarding prion-prion interactions and formation of prions (Du and Li 2014;Nizhnikov et al 2016;Du et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of [SWI + ] and Swi1 as its prion determinant in yeast was the first identification of a global transcriptional regulator being able to form a prion (Du et al 2008). A small, asparagine-rich extreme amino-terminal region has been described as the major determinant of [SWI + ], and the ability of this region to propagate and maintain [SWI + ] is notable (Crow, Du and Li 2011;Valtierra, Du and Li 2017). [SWI + ] has also displayed important and varied interplay with other yeast prions including [PSI + ] and [RNQ + ]-developing the knowledge regarding prion-prion interactions and formation of prions (Du and Li 2014;Nizhnikov et al 2016;Du et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This capability was demonstrated via the classic Sup35 assay (Sondheimer and Lindquist 2000). In this assay, Swi1 1-38 , Swi1 1-32 and Sw1 1-31 all could recapitulate the [PSI + ]like phenotype as artificial prions ([SPS + ]) when fused with the MC region of Sup35 (Valtierra, Du and Li 2017). Further work is necessary to determine the roles of the extreme amino-terminal region (∼30 amino acids) in Swi1 prion de novo formation and propagation regarding the prion-forming frequency, stabilization and interactions with other proteins.…”
Section: Defining the Prion Domain Of Swi1mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that the N-region contains the prion domain (PrD) that is essential and sufficient for [ SWI + ] formation and propagation [ 20 , 21 ]. Intriguingly, a region that contains the first 32–38 amino acids of Swi1 is largely asparagine-rich, can join [ SWI + ] aggregates, propagate the [ SWI + ] conformation, and act as a transferable PrD [ 22 , 23 , 24 ]. [ SWI + ] relies on chaperones for its propagation and is highly sensitive to alterations in the Hsp70 chaperone system activity [ 14 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its amino-terminal region enriched in asparagine is dispensable for the remodeling function and contains an amyloid core domain that can form amyloid in vitro 27 , 28 . Swi1 harbors a prion domain (PrD) at its N-terminus and the first 30 or so residues is sufficient to support the prion propagation 29 , 30 . The C-terminal region is not involved in the prion formation or transmission but is essential for normal function of Swi1 27 , 31 .…”
Section: Introductionmentioning
confidence: 99%